Path Analysis Between Job Satisfaction And Loyalty With Work Environment And Culture As Explanatory Variables - Fathurahman, Muhammad (PRODUKTIF: Jurnal Kepegawaian dan Organisasi, 2022)
Organizational culture and work environment are two main things in building social organization. Whether we realize it or not, the organization is a place where everyone interacts within the scope of work. Therefore there will be a direct relationship between employees, leaders and other parties. So that it takes togetherness of all parties to be able to socialize well, so as to create mutual comfort. Based on this background, this research was actually conducted with the aim of analyzing the ideal model in improving performance based on environmental factors and work culture. To answer this objective, a quantitative method was established as the basis of the research. Meanwhile, in analyzing the research data, linear regression statistical analysis was used. The unit of analysis in this study were 63 employees of the National Zakat Agency. Data were obtained through a simple random technique, through the distribution of questionnaires. The results of the study suggest that the work environment has the best path in increasing loyalty. This is because the work environment has a direct impact on the daily work of employees. Thus, a good and comfortable work environment is the need of all employees, which must be maintained together. In path analysis, satisfaction becomes a good model as a reinforcement of loyal behavior.